1980
DOI: 10.1021/ma60077a018
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 (T1p) Experiments on Solid Glassy Polymers

Abstract: Experimental cross-polarization transfer rates, from protons in the local dipolar field to carbons in an applied radio-frequency field, can be used to determine quantitatively the relative contributions of spin-lattice and spin-spin processes to carbon Tlp relaxation. We show that this procedure is to be preferred to determinations based either on various semiquantitative arguments, on the analysis of the Hi dependence of Tlp, or on the use of theoretically calculated rigid-lattice spin-spin transfer rates. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 9 publications
1
80
0
Order By: Relevance
“…By spin alignment measurements we could prove, in fact, that the C-CH 3 bond direction must be fixed on a timescale of at least 50 ms at 380 K, this limit -againbeing due to spin-lattice relaxation. The macromolecular chains must, therefore, be essentially interlocked in the glassy state [76]. We do not find small angle fluctuations as recently discussed by Schaefer et al [77], employing magic angle spinning ~3C NMR at room temperature, making use of 13C-1H dipolar coupling.…”
Section: Molecular Motion In Polycarbonatesupporting
confidence: 58%
“…By spin alignment measurements we could prove, in fact, that the C-CH 3 bond direction must be fixed on a timescale of at least 50 ms at 380 K, this limit -againbeing due to spin-lattice relaxation. The macromolecular chains must, therefore, be essentially interlocked in the glassy state [76]. We do not find small angle fluctuations as recently discussed by Schaefer et al [77], employing magic angle spinning ~3C NMR at room temperature, making use of 13C-1H dipolar coupling.…”
Section: Molecular Motion In Polycarbonatesupporting
confidence: 58%
“…As a result of this there may be contributions from transverse relaxation effects as well as spin-lattice effects. 19 For a truly rigid system it would be expected that the size of this effect would depend on the number of attached protons.…”
Section: Solid State Nmr Spectroscopymentioning
confidence: 99%
“…Therefore was focussed our attention on the phenylene motion which has not been so far defined [1,2,6]. The repeat unit of polycarbonate, selectively deuterated at the phenylene ring (henceforth denoted by PC 4) is depicted in Figure 1.2H NMR line shape studies of the methyl groups are reported elsewhere [5].…”
Section: Introductionmentioning
confidence: 99%